Childhood maltreatment interacts with hypothalamic-pituitary-adrenal axis negative feedback and major depression: effects on cognitive performance. Issue 1 (1st January 2021) - Salvat-Pujol, Neus; Labad, Javier; Urretavizcaya, Mikel; de Arriba-Arnau, Aida; Segalàs, Cinto; Real, Eva; Ferrer, Alex; Crespo, José M.; Jiménez-Murcia, Susana; Soriano-Mas, Carles; Menchón, José M.; Soria, Virginia
ABSTRACT: Background : Childhood maltreatment (CM) is associated with impaired hypothalamic-pituitary-adrenal (HPA) axis negative feedback and cognitive dysfunction, resembling those abnormalities linked to major depressive disorder (MDD). Objectives : We aimed to assess the potential modulating effects of MDD diagnosis or HPA axis function in the association between different types of CM and cognitive performance in adulthood. Methods : Sixty-eight MDD patients and 87 healthy controls were recruited. CM was assessed with the Childhood Trauma Questionnaire. We obtained three latent variables for neuropsychological performance (verbal memory, visual memory and executive function/processing speed) after running a confirmatory factor analysis with cognitive tests applied. Dexamethasone suppression test ratio (DSTR) was performed using dexamethasone 0.25 mg. Results : Different types of CM had different effects on cognition, modulated by MDD diagnosis and HPA axis function. Individuals with physical maltreatment and MDD presented with enhanced cognition in certain domains. The DSTR differentially modulated the association between visual memory and physical neglect or sexual abuse. Conclusions : HPA axis-related neurobiological mechanisms leading to cognitive impairment might differ depending upon the type of CM. Our results suggest a need for early assessment and intervention on cognition and resilience mechanisms in individuals exposed to CM to minimize its deleterious and lasting effects. HIGHLIGHTS: We studied the effects of childhood maltreatment (CM), HPA axis feedback (DST), and depression on cognition. Different types of CM had a distinct impact on cognitive performance. MDD diagnosis and DST modulated the association between CM and cognition.